How Does Grit Relate to The Psychological Well-being of Students Who Are Writing Thesis? - Shiddiqoh, Farah; -, Komarudin (Personifikasi: Jurnal Ilmu Psikologi, 2025)
In compiling and writing an undergraduate thesis, final-year students tend to encounter several problems. Those problems will come with pressure both from outside and from within, resulting in students' personality factors not being achieved, where in advance, these conditions trigger disruption of students' psychological well-being. Final-year students who are writing a thesis need to have a personality in the form of "GRIT." Grit is a personality factor that describes differences in individual abilities in achieving academic success. This research aimed to determine the relationship between Grit and psychological well-being in final-year students writing their theses. This research used a quantitative correlational method with a sample of 222 students, using an accidental sampling technique. The data collection process in this study was measured using the psychological well-being scale and the Grit scale modified from previous research. Data analysis techniques for hypothesis testing in this research used Pearson's Product Moment with the SPSS 26.0 on Windows application.  The research results show a correlation coefficient (r) of 0.617 with a p value of 0.000 (P0.01), which means there is a significant relationship between grit and psychological well-being in students who are doing their thesis. As a suggestion for future researchers, they may conduct qualitative research to get an in-depth picture of the Grit phenomenon with psychological well-being.